2019
DOI: 10.20473/jaki.v7i2.2019.155-161
|View full text |Cite
|
Sign up to set email alerts
|

Resources Required in Clinical Pathway for Typhoid Fever Treatment at Kaliwates General Hospital in 2017

Abstract: Background: A clinical pathway is a concept of an integrated service which describes the stages of healthcare services from the admission until the return of  patients based on the medical service standards and evidence-based nursing care with measurable results. Kaliwates General Hospital is an accredited hospital with a clinical pathway. Typhoid case was the highest disease in 2017 at Kaliwates General Hospital.Aims: This study aims to describe the resources at Kaliwates General Hospital in the implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…From this study, it is known that doctors, nurses, and pharmacists at [12]. In comparison, a study regarding typhoid CP in a hospital in Indonesia stated that the healthcare personnel's level of knowledge in their hospital was moderate [9]. Knowledge contributes to the employee's performance of the organization, which starts through the individual aspect [13], [14].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…From this study, it is known that doctors, nurses, and pharmacists at [12]. In comparison, a study regarding typhoid CP in a hospital in Indonesia stated that the healthcare personnel's level of knowledge in their hospital was moderate [9]. Knowledge contributes to the employee's performance of the organization, which starts through the individual aspect [13], [14].…”
Section: Discussionmentioning
confidence: 93%
“…It was suggested that socialization intervention only was not sufficient to achieve organizational goals. CPs will not be successfully implemented if it is not accompanied by the readiness of the hospital as an organization, implementers, and medical personnel who are specifically involved and play roles in the CPs implementation [9].…”
Section: Cp Implementation In Usu Hospital Contextmentioning
confidence: 99%